P.225 Factors Contributing to Prolonged Length of Stay in Adults Undergoing Spine Surgery: Results from a Quaternary Spinal Care Center. (November 2021) - Hindi, MN; Dandurand, C; Paquette, S; Kwon, B; Ailon, T; Dvorak, M; Dea, N; Charest-Morin, R; Fisher, C; Boyd, M; Street, J
Abstract : Background: Prolonged length of stay (LOS) is associated with increased resource utilization and worse outcomes. The goal of this study is identifying patient, surgical and systemic factors associated with prolonged LOS overall and per diagnostic category for adults admitted to a quaternary spinal care center. Methods: We performed a retrospective analysis on 13, 493 admissions from 2006 to 2019. Factors analyzed included patient age, sex, emergency vs elective admission, diagnostic category (degenerative, deformity, oncology, trauma), presence of neurological deficits in trauma patients, ASIA score, operative management and duration, blood loss, and adverse events (AEs). Univariate and multivariate analyses determined factors associated with prolonged LOS. Results: Overall mean LOS (±SD) was 15.80 (±34.03) days. Through multivariate analyses, predictors of prolonged LOS were advanced age (p<0.001), emergency admission (p<0.001), advanced ASIA score (p<0.001), operative management (p=0.043), and presence of AEs (p<0.001), including SSI (p=0.001), other infections (systemic and UTI) (p<0.001), delirium (p=0.006), and pneumonia (p<0.001). The effects of age, emergency admission, and AEs on LOS differed by diagnostic category. Conclusions: Understanding patient and disease factors that affect LOS provides opportunities for QI intervention and allows for an informed preoperative discussion with patients. Future interventions can be targeted to maximize patient outcomes, optimize care quality, and decrease costs.